DETERMINATION OF HEAVY METALS’ POLLUTION FROM MOTOR PARKS’ SOILS OF GOMBE METROPOLIS, NIGERIA - SEYDOU, HANKOURAOU; SALIHU, JIBRIN (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
Heavy metals are regarded as the most concerned of the pollutant in many environments today because of the presence of industries, markets, motor parks, mining and other human activities. The study determined the heavy metals pollution in the uppermost soils of urban Motor Park in Gombe metropolis. Random sampling techniques were used in collecting the samples in all the sample points at each of the four packs and the control sides. A mass concentration profiles of 15 elements (Sn, Sb, Ag, Cr, Cd, Zr, Co, Rb, As, Rb, Ag, Sr, Bi, Se, W, and V) were established from the soil using Niton X-ray Fluorescence Techniques (NXRF). The degrees of heavy metal contamination in soils were calculated using selected pollution indices Geoaccumulation index (Igeo), Enrichment Factor (EF), with reference to geochemical background enrichment factor. The lowest to the highest mean ranges of Zirconium, Silicon, Antimony, Cadmium, Arsenic, cobalt, chromium, and Rubidium were found to be 54.54 ppm – 473.74 ppm, 1646 ppm -1478897 ppm, 2.43 ppm – 5.51 ppm, 1.32 ppm – 461ppm, 0.5 ppm – 1.00 ppm, 36.07 ppm – 21.01 ppm, 12.92 ppm – 17.72 ppm, 8.82 ppm - 136.06 ppm, and 3.58 – 35.54 ppm respectively, with a mean of 218.5 ppm, 5171.07 ppm, 3.9 ppm, 1.63 ppm, 1.30 ppm, 42.69 ppm, 6.13 ppm, 31.39 ppm, 7.97 ppm, 39.66 ppm in given order above. The results indicated that surface soils of Gombe Urban motor packs were moderately polluted by particulates containing Cd, Cr, Zr, Ag, Rb, Sn, Zr, Ag and As. Contamination with As, Ag, Sn, Sb, Co, and Sr was moderate (Igeo >4 and PLI>1). These metals may cause harmful effects on the populace using or earning their daily living in those areas. The pre-industrial activities such as improper disposal of toxic lubricants, heaps of metals scraps, electronic waste, and sanitization of vehicles that might have transported agricultural chemicals such as fertilizers, pesticides, and herbicides are important causative agents for releasing heavy metals on the studied areas.